‘Nurr’ishing T(reg) cells: Nr4a transcription factors control Foxp3 expression - Bandukwala, Hozefa S (2013)
The Nr4a family of transcription factors transactivate expression of the transcription factor Foxp3 and are essential for the generation of regulatory T cells. Mice deficient in all three members of the Nr4a family develop massive multiorgan inflammation.